Intelligent Feedback Scheduling of Control Tasks - Telchy, Fatin I. (Iraqi Journal for Electrical and Electronic Engineering, 2014)
An efficient feedback scheduling scheme based on the proposed Feed Forward Neural Network (FFNN) scheme is employed to improve the overall control performance while minimizing the overhead of feedback scheduling which exposed using the optimal solutions obtained offline by mathematical optimization methods. The previously described FFNN is employed to adapt online the sampling periods of concurrent control tasks with respect to changes in computing resource availability. The proposed intelligent scheduler will be examined with different optimization algorithms. An inverted pendulum cost function is used in these experiments. Then, simulation of three inverted pendulums as intelligent Real Time System (RTS) is described in details. Numerical simulation results demonstrates that the proposed scheme can reduce the computational overhead significantly while delivering almost the same overall control performance as compared to optimal feedback scheduling